(untitled) (Research, Society and Development, 2022)
As a result of the teachers’ search for technological resources that help learning in the Mathematics classroom and the problems faced, such as the difficulty in helping all students in increasingly overcrowded classrooms. The main objective of this work is to analyze the OneNote software as a possible instrument to be used in mathematics classes. The method used to analyze this tool was the Instrumental Approach, which allowed, through its usage schemes and schemes of instrumental collective activities, to carry out the process of transforming the tool into a useful instrument in the classroom. By carrying out an internal research creating conjectures of situations that could occur with the use of OneNote in the classroom, he realized that the "Mathematics" tool of the software would allow a better help to clarify doubts, concluding that this instrument will serve as a great support in math classes involving content on equations, inequalities, functions and analytical geometry.